Assessment of Net Energy Metering on Distribution Network Losses - Celvakumaran P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; Electric load flow; Electric power distribution; Intelligent systems; Process control; Dynamic network characteristics; Grid loss; Load flow analysis; Net metering; Operating condition; Solar PVs; Stability analysis; Steady-state operation; Electric power transmission networks